FRAME DAN PERSPEKTIF MASJID JOGOKARIYAN PADA ULASAN GOOGLE MAPS; KAJIAN LINGUISTIK KORPUS - Hidayat, Rahmat; Roselani, Ni Gusti Ayu (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2025)
The Jogokariyan Mosque is a religious tourism location in Yogyakarta. Many people already know the Jogokariyan mosque both from Yogyakarta residents and outside Yogyakarta. Some visitors have different views about the Jogokariyan mosque. The difference can be seen from the linguistic expressions of visitors, both from direct interviews, netizens' comments on social media and reviews on Google Maps. The opinions of visitors on the Google Maps application of the Jogokariyan Mosque show individual thoughts on the mosque. This research aims to find out the thoughts of visitors to the Jogokariyan Mosque, especially from the point of view of google maps review. The research data is in the form of visitor reviews, which are collected through transcription techniques. The collected data were analyzed in two stages, first, classified using a corpus linguistic approach using Antconc_64bit software, second, analyzed using a cognitive linguistic approach, Frame theory and Fillmore Perspective. The results of the study showed 100 keywords classified based on word rank and word similarity. The next results show that the keyword